Assuming an equation with one side as a squared variable expression and the other side as a numeric expression, which of the following statements is correct? Statement
3 answers
is missing in the question. Can you please provide the options?
Solve the following quadratic equation using square roots: −9 (x−3)2−4=−4 .(1 point)
To solve the quadratic equation "-9(x-3)^2 - 4 = -4," we can follow these steps:
1. Start by adding 4 to both sides of the equation to isolate the squared variable expression on one side:
-9(x-3)^2 - 4 + 4 = -4 + 4
-9(x-3)^2 = 0
2. Divide both sides of the equation by -9 to eliminate the coefficient of the squared expression:
-9(x-3)^2 / -9 = 0 / -9
(x-3)^2 = 0
3. Take the square root of both sides of the equation to solve for x:
√((x-3)^2) = √0
x-3 = 0
4. Add 3 to both sides of the equation to isolate x:
x - 3 + 3 = 0 + 3
x = 3
Therefore, the solution to the quadratic equation is x = 3.
1. Start by adding 4 to both sides of the equation to isolate the squared variable expression on one side:
-9(x-3)^2 - 4 + 4 = -4 + 4
-9(x-3)^2 = 0
2. Divide both sides of the equation by -9 to eliminate the coefficient of the squared expression:
-9(x-3)^2 / -9 = 0 / -9
(x-3)^2 = 0
3. Take the square root of both sides of the equation to solve for x:
√((x-3)^2) = √0
x-3 = 0
4. Add 3 to both sides of the equation to isolate x:
x - 3 + 3 = 0 + 3
x = 3
Therefore, the solution to the quadratic equation is x = 3.